Sodium Doping-Enhanced Emission Efficiency and Stability of CsPbBr3 Nanocrystals for White Light-Emitting Devices - Li, Sen; Shi, Zhifeng; Zhang, Fei; Wang, Lintao; Ma, Zhuangzhuang; Yang, Dongwen; Yao, Zhiqiang; Wu, Di; Xu, Ting-Ting; Tian, Yongtao; Zhang, Yuantao; Shan, Chongxin; et al. (Chemistry of materials, 2019)
In this work, an effective strategy through doping of univalent Na+ ions, which are stable against oxidation and reduction, was proposed to enhance the emission efficiency and stability of orthorhombic CsPbBr3 nanocrystals (NCs). Compared with the fresh CsPbBr3 NCs, a better color purity and a higher photoluminescence quantum yield were achieved, accompanied with a gradual blue shift of the emission peak with an increasing Na+ doping ratio. On the one hand, the passivation effect with Na+ doping substantially reduces the nonradiative trap centers in NCs. On the other hand, the density functional theory calculations indicate that the doping of Na+ ions forms the energetically preferred substitution NaPb, which increases the optical band gap of CsPbBr3 and the diffusion barrier of Br vacancy in CsPbBr3 structures. Experimentally, the as-synthesized Na+-doped CsPbBr3 NCs present obvious enhancements in stability against ultraviolet light, heat, and moisture. The above advantages allow us to use such CsPbBr3:Na NCs as solid-state phosphors for white light-emitting device (WLED) applications. Finally, the prepared WLED exhibits a pure white light with Commission International de I’Eclairage color coordinates at (0.31, 0.33), with a color temperature of 6652 K, a color rendering index of 75.2, and a high power efficiency of 67.3 l m/W. More importantly, the WLED shows only 15% decay after continuous runs for as long as 500 h, which demonstrates a great superiority to the reference device with the fresh CsPbBr3 NCs as the phosphors. The approach used here provides an effective strategy to improve the emission efficiency and stability of perovskite NCs, showing promising potentials for their applications in lighting and display fields.